Method for preparing nano-particle modified graphene reinforced magnesium-based composite material

By introducing uniformly distributed ZrO2 nanoparticles on the graphene surface, modifying graphene zirconia nanoparticles and adding them to the magnesium alloy matrix, the problem of weak bonding between graphene and magnesium alloy is solved, and the mechanical properties of the composite material are significantly improved.

CN119614933APending Publication Date: 2025-03-14YICHUN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411956621.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The interface bond between graphene and magnesium alloy is weak and easy to agglomerate, resulting in poor strengthening effect in the preparation and application of high-performance graphene-magnesium alloy composites.

Method used

The uniformly distributed ZrO2 nanoparticles are introduced on the surface of the graphene, and the zirconia nanoparticles modified graphene is formed through ultrasonic dispersion, addition of complexing agent, dropwise addition of ammonia water, and added to the magnesium alloy matrix to improve the interface bonding strength between graphene and magnesium matrix.

Benefits of technology

通过纳米颗粒改性石墨烯,显著改进了石墨烯与镁基体的界面结合,细化晶粒组织,获得力学性能优异的石墨烯增强镁基复合材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614933A_ABST
    Figure CN119614933A_ABST
Patent Text Reader

Abstract

The method comprises the following steps: adding graphene oxide into deionized water, carrying out ultrasonic treatment to uniformly disperse the graphene oxide, then adding EDTA, carrying out mechanical stirring and ultrasonic dispersion and uniform mixing, then adding a proper amount of Zr salt, heating in a water bath kettle, and carrying out mechanical stirring and uniform mixing, so as to obtain the nano-particle modified graphene reinforced magnesium-based composite material. Dropwise adding an ammonia water solution to obtain a nano-particle modified graphene precursor precipitate, and then filtering, drying and sintering to obtain the nano-particle modified graphene reinforcement. And adding the reinforcement into magnesium alloy gold powder, and carrying out cold pressing, hot pressing sintering and hot extrusion forming to obtain the nano-particle modified graphene reinforced magnesium-based composite material. The cost is low, nanoparticles are uniformly dispersed on the surface of graphene, graphene can be well pinned in a magnesium matrix, the interface bonding quality is improved, grain refinement is remarkable, and the composite material is excellent in comprehensive mechanical property and has a very good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal material preparation, and particularly relates to a method for preparing a magnesium alloy composite material. Background Art

[0002] New materials have become one of the main driving forces. The rapid development of aerospace, low-altitude aircraft, new energy vehicles, etc. has led to a stronger demand for new materials, especially lightweight and high-strength magnesium alloy composites. As a new generation of magnesium-based composites with great development potential, it has received key development in the application field due to its high specific stiffness / specific strength, low density and environmental friendliness. Since its discovery, graphene has been an ideal reinforcement for the preparation of high-performance magnesium alloy composites due to its excellent comprehensive mechanical properties, elastic modulus exceeding 1TPa, and strength more than 100 times that of steel. However, graphene has a weak interface bonding with magnesium alloys and is easy to agglomerate, resulting in poor strengthening effect. These have become technical difficulties in the preparation and application of high-performance graphene-magnesium alloy composites. Summary of the invention

[0003] The purpose of the present invention is to provide a method for nanoparticle modified graphene to enhance magnesium-based composite materials. Uniformly distributed ZrO2 nanoparticles are introduced on the surface of graphene, and zirconium oxide nanoparticles are uniformly dispersed on the surface of graphene and added to a magnesium alloy matrix, which can better pin graphene in the magnesium matrix, so that graphene and the magnesium matrix form a strong interface bond. At the same time, the grain structure is refined to obtain a graphene-enhanced magnesium-based composite material with excellent mechanical properties.

[0004] The present invention is achieved through the following technical solutions.

[0005] The method for preparing a nanoparticle-modified graphene-reinforced magnesium-based composite material according to the present invention comprises the following steps.

[0006] 1) Ultrasonic dispersion: Add graphene oxide to deionized water at a ratio of 1 g: 1000-2000 mL, with a power of 200 W and ultrasonic dispersion treatment for 0.5-2 h to obtain a uniformly dispersed graphene oxide aqueous solution.

[0007] 2) Adding a complexing agent: Add ethylenediaminetetraacetic acid (EDTA) to the graphene oxide aqueous solution obtained in step 1) at a weight ratio of graphene oxide to ethylenediaminetetraacetic acid (EDTA) = 1:1~2, and perform mechanical stirring (rate 100 rpm) + ultrasonic treatment (power 200 W) for 0.3-0.5 h to mix the graphene oxide and the complexing agent EDTA evenly.

[0008] 3) Adding Zr salt: Add Zr salt with a molar ratio of graphene oxide to Zr ions of 1:1 to the graphene oxide mixed solution obtained in step 2), and place it in a 90-100°C water bath and mechanically stir for 0.5-1h (stirring rate 100rpm).

[0009] 4) Adding ammonia water: gradually add 2 mol / L ammonia water solution (at a rate of 5 ml / min) to the mixed solution obtained in step 3) until the pH value of the solution reaches 11, stop adding ammonia water solution, let stand - pour out the upper clear liquid - add deionized water to wash - let stand - pour out the long layer of clear liquid - add deionized water to wash, repeat until the pH value = 7, and then filter to obtain zirconium oxide nanoparticles modified graphene structure precursor.

[0010] 5) Drying treatment: The precursor obtained in step 4) is placed in a vacuum freeze dryer and freeze-dried for 12 hours at -50°C to obtain a dry precursor.

[0011] 6) Sintering treatment: The dried precursor obtained in step 5) is placed in a vacuum sintering furnace, and sintered at 650-750° C. for 1-2 hours under argon protection to obtain a nanoparticle-modified graphene reinforcement.

[0012] 7) Dispersion of nanoparticle-modified graphene: Add nanoparticle-modified graphene into ethanol at a ratio of nanoparticle-modified graphene: ethanol = 0.1-1.0 g: 500-2000 mL, and perform ultrasonic dispersion for 0.3-0.5 h at a power of 1100 W to obtain a uniformly dispersed mixed solution.

[0013] 8) Nanoparticle modified graphene and magnesium alloy powder are uniformly dispersed: magnesium alloy powder (particle size of 500 mesh) is added to the mixed solution obtained in step 7) at a weight ratio of nanoparticle modified graphene: magnesium alloy powder = 0.1~1:100, and mechanically stirred (speed 100-500rpm) for 2-3h to obtain a relatively uniformly dispersed modified graphene-magnesium alloy powder mixed slurry, which is then filtered and vacuum dried (dried at 80℃ for 0.5-1h) to obtain a modified graphene-magnesium alloy powder mixture.

[0014] 9) Hot pressing and sintering: The modified graphene-magnesium alloy powder mixture is added to a mold with a diameter of 40-50 mm and hot pressed and sintered at a pressure of 20-50 MPa and a temperature of 400-500°C.

[0015] 10) Hot extrusion forming: The composite material obtained in step 10) is kept at 450-500° C. for 1-2 hours and then hot extruded to obtain a nanoparticle-modified graphene-reinforced magnesium-based composite material. The hot extrusion rate is 0.5-1 mm / min and the extrusion temperature is 450-500° C.

[0016] The invention has low cost, and the zirconium oxide nanoparticles are evenly dispersed on the graphene surface. When added to the magnesium alloy matrix, the graphene can be better pinned in the magnesium matrix, so that the graphene and the magnesium matrix form a strong interface bond, which effectively improves the technical problem of weak interface bond between the graphene and the magnesium matrix. The grains are significantly refined, and the composite material has excellent comprehensive mechanical properties, and has very good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the zirconium oxide nanoparticles modified graphene prepared by the present invention and in the magnesium matrix. From left to right: graphene oxide → graphene surface adsorbed Zr 4+ → Zirconia nanoparticles modified graphene → Magnesium-based composites.

[0018] Figure 2 This is the TEM morphology of zirconium oxide nanoparticle-modified graphene prepared in the present invention.

[0019] Figure 3 The metallographic structure of the zirconium oxide nanoparticle modified graphene reinforced magnesium-based composite material prepared by the present invention. The left picture is the AZ91 matrix alloy, and the right picture is the 0.5wt.% modified graphene reinforced AZ91 magnesium alloy composite material. DETAILED DESCRIPTION

[0020] The present invention will be further illustrated by the following examples. Example 1

[0021] 1) Ultrasonic dispersion: Add 1 g of graphene oxide into 1500 mL of deionized water and perform ultrasonic dispersion (power 200 W) for 1 h to obtain a uniformly dispersed graphene oxide aqueous solution.

[0022] 2) Adding a complexing agent: Add 1 g of ethylenediaminetetraacetic acid (EDTA) to the graphene oxide aqueous solution obtained in step 1), and perform mechanical stirring (rate 100 rpm) + ultrasonic treatment (power 200 W) for 0.4 h to mix the graphene oxide and the complexing agent EDTA evenly.

[0023] 3) Adding Zr salt: Add Zr salt with a molar ratio of graphene oxide to Zr ions of 1:1 to the graphene oxide mixed solution obtained in step 2), and place it in a 95°C water bath and mechanically stir for 0.5h (stirring rate remains unchanged).

[0024] 4) Adding ammonia water: gradually add 2 mol / L ammonia water solution (at a rate of 5 ml / min) to the mixed solution obtained in step 3) until the pH value of the solution reaches 11, stop adding ammonia water solution, let stand - pour out the upper clear liquid - add deionized water to wash - let stand - pour out the long layer clear liquid - add deionized water to wash, repeat until the pH value = 7, and then filter to obtain the zirconium oxide network pinned graphene structure precursor.

[0025] 5) Drying treatment: The precursor obtained in step 4) is placed in a vacuum freeze dryer and freeze-dried for 12 hours at -50°C to obtain a dry precursor.

[0026] 6) Sintering treatment: The dried precursor obtained in step 5) is placed in a vacuum sintering furnace, and sintered at 650-750° C. for 1.5 h under argon protection to obtain a zirconium oxide nanoparticle-modified graphene reinforcement.

[0027] 7) Dispersion of zirconium nanoparticle-modified graphene: 0.1 g of nanoparticle-modified graphene was added to 800 mL of ethanol and ultrasonically dispersed for 0.4 h at a power of 1100 W to obtain a uniformly dispersed mixed solution.

[0028] 8) Nanoparticle modified graphene and magnesium alloy powder are uniformly dispersed: 99.9 g of magnesium alloy powder (particle size is 500 mesh) is added to the above-obtained mixed solution, and mechanically stirred (speed 150 rpm) for 2 hours to obtain a relatively uniformly dispersed modified graphene-magnesium alloy powder mixed slurry, which is then filtered and vacuum dried (dried at 80°C for 1 hour) to obtain a modified graphene-magnesium alloy powder mixture.

[0029] 9) Hot pressing and sintering: The modified graphene-magnesium alloy powder mixture is added to a mold with a diameter of 40 mm and hot pressed and sintered at a pressure of 30 MPa and a temperature of 450°C.

[0030] 10) Hot extrusion forming: The composite material obtained in step 9) is kept at 450°C for 2h and then hot extruded to obtain a nanoparticle-modified graphene-reinforced magnesium-based composite material, with a hot extrusion rate of 1 mm / min and an extrusion temperature of 450°C. The composite material was tested for its mechanical properties, and its tensile strength reached 270-310 MPa, its elongation reached 10.5-13.5%, and its hardness was 85-99 HV, indicating that it is a composite material with good mechanical properties. Example 2

[0031] 1) Ultrasonic dispersion: Add 1 g of graphene oxide into 1500 mL of deionized water and perform ultrasonic dispersion (power 200 W) for 1 h to obtain a uniformly dispersed graphene oxide aqueous solution.

[0032] 2) Adding a complexing agent: Add 1 g of ethylenediaminetetraacetic acid (EDTA) to the graphene oxide aqueous solution obtained in step 1), and perform mechanical stirring (rate 100 rpm) + ultrasonic treatment (power 200 W) for 0.4 h to mix the graphene oxide and the complexing agent EDTA evenly.

[0033] 3) Adding Zr salt: Add Zr salt with a molar ratio of graphene oxide to Zr ions of 1:1 to the graphene oxide mixed solution obtained in step 2), and place it in a 95°C water bath and mechanically stir for 0.5h (stirring rate remains unchanged).

[0034] 4) Adding ammonia water: gradually add 2 mol / L ammonia water solution (at a rate of 5 ml / min) to the mixed solution obtained in step 3) until the pH value of the solution reaches 11, stop adding ammonia water solution, let stand - pour out the upper clear liquid - add deionized water to wash - let stand - pour out the long layer clear liquid - add deionized water to wash, repeat until the pH value = 7, and then filter to obtain the nanoparticle-modified graphene structure precursor.

[0035] 5) Drying treatment: The precursor obtained in step 4) is placed in a vacuum freeze dryer and freeze-dried for 12 hours at -50°C to obtain a dry precursor.

[0036] 6) Sintering treatment: The dried precursor obtained in step 5) is placed in a vacuum sintering furnace, and sintered at 650-750° C. for 1.5 h under argon protection to obtain a zirconium oxide nanoparticle-modified graphene reinforcement.

[0037] 7) Dispersion of nanoparticle-modified graphene: 0.3 g of nanoparticle-modified graphene was added to 800 mL of ethanol and ultrasonically dispersed for 0.4 h at a power of 1100 W to obtain a uniformly dispersed mixed solution.

[0038] 8) Nanoparticle modified graphene and magnesium alloy powder are uniformly dispersed: 99.7 g of magnesium alloy powder (particle size is 500 mesh) is added to the above-obtained mixed solution, and mechanically stirred (speed 150 rpm) for 2 hours to obtain a relatively uniformly dispersed modified graphene-magnesium alloy powder mixed slurry, which is then filtered and vacuum dried (dried at 80°C for 1 hour) to obtain a modified graphene-magnesium alloy powder mixture.

[0039] 9) Hot pressing and sintering: The modified graphene-magnesium alloy powder mixture is added to a mold with a diameter of 40 mm and hot pressed and sintered at a pressure of 30 MPa and a temperature of 450°C.

[0040] 10) Hot extrusion forming: The composite material obtained in step 9) is kept at 450°C for 2h and then hot extruded to obtain a nanoparticle-modified graphene-reinforced magnesium-based composite material, with a hot extrusion rate of 1 mm / min and an extrusion temperature of 450°C. The composite material was tested for its mechanical properties, and its tensile strength reached 300-330 MPa, its elongation reached 13.5-14.5%, and its hardness was 89-105 HV, indicating that it is a composite material with excellent mechanical properties. Example 3

[0041] 1) Ultrasonic dispersion: Add 1 g of graphene oxide into 1500 mL of deionized water and perform ultrasonic dispersion (power 200 W) for 1 h to obtain a uniformly dispersed graphene oxide aqueous solution.

[0042] 2) Adding a complexing agent: Add 1 g of ethylenediaminetetraacetic acid (EDTA) to the graphene oxide aqueous solution obtained in step 1), and perform mechanical stirring (rate 100 rpm) + ultrasonic treatment (power 200 W) for 0.4 h to mix the graphene oxide and the complexing agent EDTA evenly.

[0043] 3) Adding Zr salt: Add Zr salt with a molar ratio of graphene oxide to Zr ions of 1:1 to the graphene oxide mixed solution obtained in step 2), and place it in a 95°C water bath and mechanically stir for 0.5h (stirring rate remains unchanged).

[0044] 4) Adding ammonia water: gradually add 2 mol / L ammonia water solution (at a rate of 5 ml / min) to the mixed solution obtained in step 3) until the pH value of the solution reaches 11, stop adding ammonia water solution, let stand - pour out the upper clear liquid - add deionized water to wash - let stand - pour out the long layer of clear liquid - add deionized water to wash, repeat until the pH value = 7, and then filter to obtain zirconium oxide nanoparticle graphene structure precursor.

[0045] 5) Drying treatment: The precursor obtained in step 4) is placed in a vacuum freeze dryer and freeze-dried for 12 hours at -50°C to obtain a dry precursor.

[0046] 6) Sintering treatment: The dried precursor obtained in step 5) is placed in a vacuum sintering furnace, and sintered at 650-750° C. for 1.5 h under argon protection to obtain a nanoparticle-modified graphene reinforcement.

[0047] 7) Dispersion of nanoparticle-modified graphene: 0.5 g of “zirconia network pinning structure” modified graphene was added to 800 mL of ethanol and ultrasonically dispersed for 0.4 h at a power of 1100 W to obtain a uniformly dispersed mixed solution.

[0048] 8) Nanoparticle modified graphene and magnesium alloy powder are uniformly dispersed: 99.5 g of magnesium alloy powder (particle size is 500 mesh) is added to the above-obtained mixed solution, and mechanically stirred (speed 150 rpm) for 2 hours to obtain a relatively uniformly dispersed modified graphene-magnesium alloy powder mixed slurry, which is then filtered and vacuum dried (dried at 80°C for 1 hour) to obtain a modified graphene-magnesium alloy powder mixture.

[0049] 9) Hot pressing and sintering: The modified graphene-magnesium alloy powder mixture is added to a mold with a diameter of 40 mm and hot pressed and sintered at a pressure of 30 MPa and a temperature of 450°C.

[0050] 10) Hot extrusion forming: The composite material obtained in step 9) is kept at 450°C for 2h and then hot extruded to obtain a nanoparticle-modified graphene-reinforced magnesium-based composite material, with a hot extrusion rate of 1 mm / min and an extrusion temperature of 450°C. The composite material was tested for its mechanical properties, and its tensile strength reached 329-350 MPa, its elongation reached 13.5-14.8%, and its hardness was 108-123 HV, indicating that it is a composite material with excellent mechanical properties.

[0051] Attached Figure 1 The schematic diagram of zirconium oxide nanoparticles modified graphene and magnesium matrix in the implementation example shows that zirconium oxide nanoparticles are evenly distributed on the graphene surface to form a new modified graphene reinforcement. When compounded into the magnesium matrix, the zirconium oxide nanoparticles and the magnesium matrix will have a slight interface reaction and the graphene will be tightly pinned in the magnesium matrix, so that the graphene and the magnesium matrix form a good interface bond, which is beneficial to improve the comprehensive mechanical properties of the composite material.

[0052] Attached Figure 2 This is the TEM morphology of zirconium oxide nanoparticle-modified graphene used in the example. The figure shows that the zirconium oxide nanoparticles are evenly distributed on the graphene surface to form a nanoparticle-modified graphene reinforcement. Figure 3 The metallographic structure of the AZ91 magnesium alloy material with 0.5wt.% addition of zirconium oxide nanoparticles modified graphene prepared under the conditions of Example 3. Compared with the AZ91 matrix alloy structure, it can be found that the grain size of the composite material is significantly finer, the fine grain strengthening is obvious, and the mechanical properties of the composite material are significantly improved.

Claims

1. A method for nanoparticle-modified graphene-enhanced magnesium-based composite material, characterized in that Follow these steps: 1) Add graphene oxide to deionized water at a ratio of 1 g of graphene oxide to ionized water of 1000-2000 mL, perform ultrasonic dispersion treatment at a power of 200 W for 0.5-2 h, and obtain a uniformly dispersed graphene oxide aqueous solution; 2) adding ethylenediaminetetraacetic acid to the graphene oxide aqueous solution obtained in step 1) at a weight ratio of graphene oxide to ethylenediaminetetraacetic acid = 1:1-2, and subjecting to mechanical stirring + ultrasonic treatment for 0.3-0.5 h, a stirring rate of 100 rpm, and an ultrasonic power of 200 W, so that the graphene oxide and ethylenediaminetetraacetic acid are evenly mixed; 3) adding a Zr salt having a molar ratio of graphene oxide to Zr ions of 1:1 to the graphene oxide mixed solution obtained in step 2), and placing the mixed solution in a 90-100° C. water bath, and mechanically stirring the mixture for 0.5-1 h at a stirring rate of 100 rpm; 4) Gradually add a 2 mol / L ammonia solution to the mixed solution obtained in step 3) at a dropping rate of 5 ml / min until the pH value of the solution reaches 11, stop adding the ammonia solution, let stand - pour out the upper clear liquid - wash with deionized water - let stand - pour out the long layer clear liquid - wash with deionized water, repeat until the pH value = 7, and then filter to obtain a precursor of zirconium oxide nanoparticle-modified graphene structure; 5) placing the precursor obtained in step 4) in a vacuum freeze dryer, and freeze drying it at -50°C for 12 hours to obtain a dry precursor; 6) placing the dried precursor obtained in step 5) in a vacuum sintering furnace, sintering at 650-750° C. for 1-2 hours under argon protection to obtain a reinforcement of nanoparticle-modified graphene; 7) Add the nanoparticle-modified graphene to ethanol at a ratio of 0.1-1.0 g of nanoparticle-modified graphene to 500-2000 mL of ethanol, and perform ultrasonic dispersion for 0.3-0.5 h at a power of 1100 W to obtain a uniformly dispersed mixed solution; 8) adding magnesium alloy powder (500 mesh) to the mixed solution obtained in step 7) at a weight ratio of nanoparticle modified graphene: magnesium alloy powder = 0.1-1:100, and mechanically stirring at a rate of 100-500 rpm for 2-3 hours to obtain a relatively uniformly dispersed modified graphene-magnesium alloy powder mixed slurry, and then filtering and drying at 80° C. for 0.5-1 hour in a vacuum dryer to obtain a modified graphene-magnesium alloy powder mixture; 9) Add the modified graphene-magnesium alloy powder mixture into a mold with a diameter of 40-50 mm and hot press sinter to form the mixture at a pressure of 20-50 MPa and a temperature of 400-500°C; 10) The composite material obtained in step 9) is kept at 450-500° C. for 1-2 hours and then hot extruded to obtain a nanoparticle-modified graphene-reinforced magnesium-based composite material, the hot extrusion rate is 0.5-1 mm / min, and the extrusion temperature is 450-500° C.